Understanding positive and negative deviations in polarity of ionic liquid mixtures by pseudo-solvent approach. Issue 34 (15th August 2016) - Beniwal, Vijay; Kumar, Anil
Abstract : Physico-chemical properties of liquid mixtures in general display large deviations from linear behaviour, arising out of complex specific and non-specific intermolecular interactions. Abstract : Physico-chemical properties of liquid mixtures in general display large deviations from linear behaviour, arising out of complex specific and non-specific intermolecular interactions. The polarity of liquid mixtures displaying large positive and negative deviations can be minimized and linear mixing can be achieved in liquids using a pseudo-solvent methodology. The work described herein is designed to investigate the influence of different physical parameters on the linear pseudo-solvent composition in ionic liquid mixtures. For this purpose, we have determined the deviations from linearity, Δ E NT values (defined as given by ) for binary mixtures of a variety of ionic liquids, including two molecular solvents, DMSO and formamide. Firstly, the investigations were carried out in three 1-butyl-3-methylimidazolium cation based aprotic ionic liquids and the roles of anionic structure and hydrogen bond acceptor basicities ( β values) of the ionic liquids were determined. The influence of the cationic structure, i.e., the hydrogen bond donor acidity ( α values) and non-associative nature of the ionic liquids, was determined using C2-methylated analogs, 1-butyl-2, 3-dimethylimidazolium cation based ionic liquids. The role of the protic nature of ionic liquids was studied in two protic ionic liquids, viz., 1-methylimidazolium formate and 1-methylimidazolium acetate. The effects of the temperature, pseudo-solvent structure and solvatochromic probe structure on the Δ E NT values were also explored.